2013
DOI: 10.1134/s1063772913070019
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of 13 high-mass stars in the Cyg OB2 association

Abstract: Aiming to explore weak spectral features of stellar and interstellar origin we used the NES echelle spectrograph of the 6-m telescope to obtain high-resolution spectra for 13 hot O3-B4 stars in the Cyg OB2 association, including a high luminous star No. 12. Velocity fields in the atmospheres and interstellar medium, characteristics of optical spectra and line profiles are investigated. The cascade star formation scheme for the association is confirmed. Evidence is presented suggesting that the hypergiant Cyg O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 57 publications
3
33
1
Order By: Relevance
“…In addition, a shallow blueshifted absorption is sometimes (but not always) present. These variations are much more extreme than those reported by Chentsov et al (2013) and Klochkova & Chentsov (2004). Finally, the He i λ 10 830 Å line profile is composed of three parts: a constant interstellar component (two deep and narrow absorption lines at velocities ∼0 and -30km s −1 ), a broad emission component on the red wing, and a complex absorption on both wings.…”
Section: Spectroscopic Featuresmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, a shallow blueshifted absorption is sometimes (but not always) present. These variations are much more extreme than those reported by Chentsov et al (2013) and Klochkova & Chentsov (2004). Finally, the He i λ 10 830 Å line profile is composed of three parts: a constant interstellar component (two deep and narrow absorption lines at velocities ∼0 and -30km s −1 ), a broad emission component on the red wing, and a complex absorption on both wings.…”
Section: Spectroscopic Featuresmentioning
confidence: 74%
“…Until now, X-ray bright wind-wind collisions have been found in massive binaries with periods of a few years (up to a decade in 9 Sgr; , not decades or centuries. Secondly, small line-profile and radial-velocity (RV) changes were reported by Klochkova & Chentsov (2004) and Chentsov et al (2013) but they could not confirm or rule out the binarity hypothesis (Chentsov et al 2013). Only a double-lined spectroscopic binary seemed excluded by the data (see also Clark et al 2012).…”
Section: Introductionmentioning
confidence: 95%
“…The figure shows that the Cyg OB2 #7 lies between the isochrones corresponding to three and four Myr and mass< 60 M , while #11 lies between four and five Myr and its mass is 40-60 M . Chentsov et al (2013) spectroscopically confirmed age differences for stars which are located in different parts of the association. The results of our numerical simulations support this conclusion and are consistent with the hypothesis of cascade star formation in the association Cyg OB2.…”
Section: Resultsmentioning
confidence: 64%
“…There is uncertainty in luminosity class of MT259. Kiminki et al (2007) estimated that MT259 is a supergiant (B0 Ib) while Chentsov et al (2013) claims that this star is a dwarf (B0 V). Our estimates of log g and L * for this star confirm the classification of Chentsov et al (2013).…”
Section: Temperatures and Luminositiesmentioning
confidence: 99%
“…Kiminki et al (2007) estimated that MT259 is a supergiant (B0 Ib) while Chentsov et al (2013) claims that this star is a dwarf (B0 V). Our estimates of log g and L * for this star confirm the classification of Chentsov et al (2013). Luminosity of MT317 is a bit higher than the tabulated value of luminosity for O8 V class, according to Martins et al (2005a).…”
Section: Temperatures and Luminositiesmentioning
confidence: 99%